Preference of birth mode and postnatal health related quality of life after one previous caesarean section in three European countries. (December 2019) - Fobelets, Maaike; Beeckman, Katrien; Buyl, Ronald; Healy, Patricia; Grylka-Baeschlin, Susanne; Nicoletti, Jane; Canepa, Matilde; Devane, Declan; Gross, Mechthild M.; Morano, Sandra; Daly, Deirdre; Begley, Cecily; et al.
Abstract: Objectives: Women who have had a caesarean section may have a preference for birth mode during their subsequent pregnancy, either 'vaginal birth after caesarean' (VBAC) or 'elective repeat caesarean section' (ERCS). A mismatch between the preferred and actual birth mode may result in an impaired postnatal Health Related Quality of Life (HRQoL). This study examined the associations between antenatal birth mode preferences, the actual birth mode and postnatal HRQoL in women with one previous caesarean section in three European countries. Design: Prospective longitudinal survey, as a part of a cluster randomised trial (OptiBIRTH) Setting: Fifteen maternity units in three European countries: Germany (5), Ireland (5) and Italy (5). Participants: Women (≥ aged 18 years) living in Germany, Ireland and Italy with one previous caesarean section. The sample consisted of 862 women with complete antenatal and postpartum data. Measurements: Women's preference for birth mode after one previous caesarean section was assessed at inclusion to the trial, and HRQoL was assessed antenatally and at three months postpartum using the Short-Form Six-Dimension health survey. Based on women's preferences and actual birth mode six groups were determined: "match VBAC-VBAC" (preference for vaginal birth, actual mode of birth vaginal birth), "match ERCS-ERCS" (preference for caesarean section, actual mode of birth elective repeat caesarean section), "match ERCS-EMCS" (preference for caesarean section, actual mode of birth emergency repeat caesarean section), "mismatch VBAC-ERCS" (preference for vaginal birth, actual mode of birth elective repeat caesarean section), "mismatch VBAC-EMCS" (preference for vaginal birth, actual mode of birth emergency repeat caesarean section) and "no preference". Associations between the preferred and actual birth mode were examined using univariate and multivariate analyses. Findings: Women with preference for vaginal birth but who gave birth by elective repeat caesarean section (mismatch VBAC-ERCS) had a lower postnatal HRQoL compared to women with a preference for vaginal birth who actually had a birth vaginally (match VBAC-VBAC, p = 0.02). Poor antenatal HRQoL scores ( p < 0.01) and maternal readmission postpartum ( p = 0.03) are cofounding factors for poorer postnatal HRQoL scores. Key conclusions: The results show that women with a preference for a vaginal birth who gave birth by an elective repeat caesarean section had a significantly lower HRQoL at three months postnatal. The long-term consequences and psychological health of women who do not achieve a vaginal birth after caesarean require further consideration and research. Implications for practice: Attention should be given to the long-term impact of a mismatch in preferred and actual mode on the psychological health of women.